2018
DOI: 10.18383/j.tom.2018.00005
|View full text |Cite
|
Sign up to set email alerts
|

Feature Tracking Cardiac MRI Reveals Abnormalities in Ventricular Function in Patients With Bicuspid Aortic Valve and Preserved Ejection Fraction

Abstract: Subclinical systolic and diastolic left ventricular (LV) dysfunction has been reported in previous echocardiographic studies on congenital bicuspid aortic valve (BAV). Patients with BAV commonly undergo evaluation with magnetic resonance imaging, and feature-tracking cardiovascular magnetic resonance (CMR-FT) is an emerging technique that assesses myocardial strain using standard cine sequences. This study investigated differences in myocardial strain between patients with BAV with preserved ejection fraction … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
11
0
2

Year Published

2019
2019
2021
2021

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 22 publications
(25 reference statements)
1
11
0
2
Order By: Relevance
“…Besides exact global and regional functional assessment, and imaging of structural changes in the myocardium (granulomas and inflammation), CMR could offer a relatively new technique of myocardial strain evaluation. Myocardial deformation could be affected earlier by slight, incipient pathological changes in the myocardium [ 11 16 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Besides exact global and regional functional assessment, and imaging of structural changes in the myocardium (granulomas and inflammation), CMR could offer a relatively new technique of myocardial strain evaluation. Myocardial deformation could be affected earlier by slight, incipient pathological changes in the myocardium [ 11 16 ].…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, CMR is restricted by lower phases, although, it profits from better imaging of the epicardial-myocardial and endocardial-myocardial tissue boundaries. CMR feature tracking (FT) is one of the myocardial deformation imaging techniques that has been tested for several clinical conditions, even in patients with preserved LV EF [ 11 , 17 – 19 ]. Nevertheless, there is very little evidence for CMR-FT in patients with recent sarcoidosis [ 20 ].…”
Section: Introductionmentioning
confidence: 99%
“…This technique of deformation measurement has been validated in different populations using speckle-tracking echocardiography [5][6][7][8][9][10][11][12][13][14][15]. More recently it was shown that GLS can also be derived from multiphase Computed Tomography (CT) datasets and conventional Cardiovascular Magnetic Resonance (CMR) steady state free-precession (SSFP) cine imaging using feature-tracking algorithms [16,17]. However, these techniques, especially GLS measurement using CT are still new and not yet very well validated.…”
Section: Introductionmentioning
confidence: 99%
“…The use of CMR-FT to evaluate LV diastolic impairment has already been performed in asymptomatic patients with BAV and preserved ejection fraction [14], evidencing an alteration in diastolic strain parameters in BAV subjects as compared to control groups [14]. Other studies revealed that CMR-FT myocardial diastolic strain analysis was able to predict adverse outcomes in patients with hypertrophic cardiomyopathy or atherosclerosis [25,26] Finally, the use of 4D Flow imaging technique offered a deeper insight on the hemodynamic consequences on intraventricular ows of different patterns of regurgitation jet.…”
Section: Discussionmentioning
confidence: 99%
“…The advanced analysis of cardiac bers deformability offered by the Cardiovascular Magnetic Resonance (CMR) feature tracking (CMR-FT) technique enables the accurate and reproducible assessment of early modi cations in both LV systolic and diastolic function [11][12][13]. CMR-FT is a postprocessing technique applied to cine steady-state free precession (cine-SSFP) sequences, which analyzes myocardial longitudinal and circumferential strain parameters throughout all phases of cardiac cycle [14].…”
Section: Introductionmentioning
confidence: 99%